Bureaucratic Reform and Digital Innovation in Travel Document Services: A Case Study of Tanjung Perak Immigration Office - Oky Sabastian; Fedianty Augustinah; Eny Hartati (International Journal of Social Science and Humanity, 2025)
This research aims to analyse the implementation of digital innovation in passport services at the Class I Immigration Office Tanjung Perak as part of bureaucratic reform and Good Governance initiatives. The study employed a qualitative case study approach, involving in-depth interviews, participatory observation, and document analysis, to assess the successes and challenges of digital systems such as SIMKIM and M-Paspor. The findings reveal that digital innovation has successfully improved operational efficiency and generally provided transparency into costs and application status, whilst reducing queuing times and increasing service speed, thereby enhancing public satisfaction and trust in immigration services. However, the innovation has not fully addressed structural and cultural bureaucratic barriers, as field officers tend to become passive when systems experience errors or delays, struggling to provide detailed explanations about issues, which results in information ambiguity and potentially undermines procedural transparency and performance accountability principles. The study concludes that bureaucratic reform in the immigration sector requires internal cultural updates and enhanced human resource competencies to support comprehensive transparency and accountability. Digital infrastructure instability and officers' discretionary authority significantly influence the effectiveness of digital innovation. Whilst digital innovation offers substantial benefits in efficiency and transparency, its success depends heavily on strengthening systems, improving human resource skills, and fostering organisational cultural change, with continuous efforts essential for achieving effective, transparent, and accountable public service.